Meeting report: 3rd international transplant conference: how much risk can you take?. (12th February 2015) - Lowe, D.; Daga, S.; Briggs, D.; Khovanova, N.; Mitchell, D.; Higgins, R.; Krishnan, N.
Summary The 3rd International Transplant Conference took place on 31st October and 1st November 2014 at the University of Warwick, Coventry, UK. Key focal points of the meeting were the exploration of the molecular basis of antibody–antigen interactions and their relation to clinical practice and to share experiences and knowledge regarding strategies to transplant the 'high‐risk' patient. In addition, lively debate sessions were hosted where controversial clinical and immunological themes were discussed by leading experts in the field.